Organized Supermarkets of South India - An Exploratory Study of the Margin Free Markets of Kerala - Paninchukunnath, Ajith (Indian Journal of Marketing, 2008)
Retailing in India is in the process of getting more organized and professional. Medium-scale retail formats such as department stores and supermarket chains have already made an appearance and are slowly changing the face of retailing in the country. South India has taken lead in establishing organized retail chains in the food and grocery category. In South India, food and grocery is the largest retail category (Rs.1, 62,313 crore) which is more organized (1.2%) than all India (0.8%). Nilgiris, FabMall, Foodworld, Trinetra, Subiksha, Margin Free, Fresh@, Namdhari are among the leading south India based food and grocery retailers. Margin Free was the first organized supermarket stores of Kerala in private sector. Margin Free is completing 13 years and have 347 outlets with a total turnover of approximately Rs. 600 crores. An exploratory study done by the author through interview method of the 15 Margin Free Markets of Kerala reveals the context under which Margin Free Markets took birth and also the reasons for its success and widespread presence in Kerala. Today Margin Free Markets have become the benchmark among supermarkets with special focus on middle class customers. Margin Free Markets also represent a unique and successful franchise model operating in India for the last thirteen years.